Gerakan Aktif Tanpa Kekerasan: Sebuah Transformasi Perjuangan Masyarakat (Kasus Masyarakat Moro-Moro Register 45 Mesuji Lampung) - Wahab, Oki Hajiansyah (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Gadjah Mada, 2013)
Forest conflict Register 45 Mesuji Lampung sticking out the end of the year is a agrarian chronic conflict and widespread impact. A conflict that has lasted more than fifteen years has spawned a variety of violence, evictions and abandonment of the constitutional rights of citizens. Moro-Moro communities are experiencing citizens entity waiver of constitutional rights, which in turn have a significant impact on their social life and consciousness. This paper uses ethnographic approach that aims to provide an overview of the successful struggle of managing conflict with social intelligence. This paper attempts to use Pierre Bourdieuâs ideas about habitus to analyze the process of transformation of the Moro-Moro communities who struggle to change the stigma of a peace maker trouble maker eventually gave birth to the support from various circles of society.